2020
DOI: 10.3390/nu12092733
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Storage Conditions on the Breast Milk Peptidome

Abstract: Human donor milk (HDM) provides appropriate nutrition and offers protective functions in preterm infants. The aim of the study is to examine the impact of different storage conditions on the stability of the human breast milk peptidome. HDM was directly frozen at −80 °C or stored at −20 °C (120 h), 4 °C (6 h), or room temperature (RT for 6 or 24 h). The milk peptidome was profiled by mass spectrometry after peptide collection by ultrafiltration. Profiling of the peptidome covered 3587 peptides corresponding to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Regardless of the samples being handled differently, the difficulties of human milk storage conditions in neonatal hospitals are widely recognized. Additionally, an investigation on the impact of storage conditions on the breast milk peptidome for MS experiments demonstrated that the majority of peptides kept quite stable when stored at −80°C, −20°C, or even at 4°C (Howland et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the samples being handled differently, the difficulties of human milk storage conditions in neonatal hospitals are widely recognized. Additionally, an investigation on the impact of storage conditions on the breast milk peptidome for MS experiments demonstrated that the majority of peptides kept quite stable when stored at −80°C, −20°C, or even at 4°C (Howland et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The lowest lysozyme level in human milk was found in samples stored at room temperature. Howland et al (2020) reported cleavage in the peptide structure of the amino acid lysine, arginine, and glutamate due to an increased thrombin activity and other protease enzymes in human milk stored at room temperature. Lysozyme or muramidase is a part of group of glycosidic hydrolases with 14.7 kDa of atomic mass in human lysozyme.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, human milk and feces need to be collected weekly and stored in the correct way to allow for microbiota analysis. Storage conditions, including temperature, have been shown to influence human milk peptidome and fecal microbiota composition [65][66][67][68]. Lastly, the absorption of proteins from human milk in the small intestine cannot be measured directly, although it may influence metabolic activity of the microbiota in the colon.…”
Section: Discussionmentioning
confidence: 99%